2008
DOI: 10.1016/j.mce.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 iodothyronine deiodinase is highly expressed in medullary thyroid carcinoma

Abstract: SummaryType II deiodinase (D2) plays a critical role in controlling intracellular T3 concentration and early studies indicated a follicular but not a parafollicular C-cell origin of D2 activity in the thyroid gland. Here, we show that D2 is highly expressed in human medullary thyroid carcinoma (MTC), a tumour that arises from the C-cells. D2 transcripts were detected in all MTC samples obtained from 12 unselected MTC patients and the levels of D2 activity were comparable to those found in surrounding normal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In one study they observed poor correlation between the low D2 mRNA level and the enzymatic activity in papillary thyroid cancer but a statistically significant correlation between D2, Pax-8, and Titf1/Nkx-2 mRNA expression suggesting a potential role in the impairment of deiodinase expression (Ambroziak et al, 2005 ). D2 is also highly expressed in human medullary thyroid carcinoma (MTC), with activity that was comparable to those found in surrounding normal follicular tissue (Meyer et al, 2008 ).…”
Section: Type 2 Deiodinasementioning
confidence: 90%
“…In one study they observed poor correlation between the low D2 mRNA level and the enzymatic activity in papillary thyroid cancer but a statistically significant correlation between D2, Pax-8, and Titf1/Nkx-2 mRNA expression suggesting a potential role in the impairment of deiodinase expression (Ambroziak et al, 2005 ). D2 is also highly expressed in human medullary thyroid carcinoma (MTC), with activity that was comparable to those found in surrounding normal follicular tissue (Meyer et al, 2008 ).…”
Section: Type 2 Deiodinasementioning
confidence: 90%
“…D2 expression has rarely been associated with neoplastic transformation. It has been found upregulated in benign hyperfunctioning thyroid nodules and in thyroid tumors including follicular thyroid carcinoma, anaplastic and medullary thyroid cancer ( 54 , 55 ), whereas its expression was lower in papillary thyroid carcinoma than in normal thyroid tissues ( 56 ). This expression pattern is consistent with D2 being a cAMP-responsive gene whose expression increases in those tumoral contexts (thyroid adenoma and follicular carcinoma) in which there is a corresponding overstimulation of the cAMP pathway ( Table 1 ).…”
Section: D2 and Cancermentioning
confidence: 99%
“…Activation of these signaling pathways produces cellular proliferation, which might favor cancer progression, and blockade of apoptotic processes and metastasis (Davis et al, 2016;Mousa et al, 2012Mousa et al, , 2018Weingarten et al, 2018). Moreover, separated evidences indicate that differences in deiodinase expression and differential splicing have been found in several cancers (Meyer et al, 2008) and increased TSHR expression have been detected in liver, ovarian, lung, and breast cancers (Table 1) (Govindaraj et al, 2012;Gyftaki et al, 2014;Kim et al, 2012;Shih et al, 2018;Tian et al, 2010). Moreover, it is known that TSHR is functional in the majority of human HCCs and that high TSHR expression is correlated with unfavorable postoperative outcome in patients with HCC receiving surgical treatment (Shih et al, 2018).…”
Section: Molecular Mechanisms Of Cancer In Thyroid Hormone Dysfunctionmentioning
confidence: 99%